2021
DOI: 10.1002/jnr.24825
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of long non‐coding RNAs and their mechanisms in Huntington's disease

Abstract: Extensive alterations in gene regulatory networks are a typical characteristic of Huntington's disease (HD); these include alterations in protein‐coding genes and poorly understood non‐coding RNAs (ncRNAs), which are associated with pathology caused by mutant huntingtin. Long non‐coding RNAs (lncRNAs) are an important class of ncRNAs involved in a variety of biological functions, including transcriptional regulation and post‐transcriptional modification of many targets, and likely contributed to the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 156 publications
(266 reference statements)
0
7
0
Order By: Relevance
“…LncRNAs have differences in size, molecular partners, and mechanism of action. According to their relative position and host protein-coding genes, lncRNAs can be divided into exons, introns, overlapping lncRNAs, and intergenic lncRNAs ( Figure 2 ; Tan et al, 2021 ).…”
Section: Lncrna Classificationmentioning
confidence: 99%
“…LncRNAs have differences in size, molecular partners, and mechanism of action. According to their relative position and host protein-coding genes, lncRNAs can be divided into exons, introns, overlapping lncRNAs, and intergenic lncRNAs ( Figure 2 ; Tan et al, 2021 ).…”
Section: Lncrna Classificationmentioning
confidence: 99%
“…The polyQ tract is responsible for the toxic gain of function and aggregation of mutant Huntingtin (mHTT) protein, leading to neuronal dysfunction and loss. The major and earliest site of pathology is the striatum, with medium spiny neurons the most vulnerable cells in HD; however, other regions of the brain, such as the cortex and cerebellum, are also affected [ 68 ].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Its overexpression and negative effect on proapoptotic PRDM5 (PR/SET Domain 5) was shown to inhibit neuronal apoptosis and alleviate acute spinal cord injury in a rat model [ 70 ], suggesting a potential neuroprotective role of DGCR5 in the neurodegeneration in HD. In turn, human accelerated region 1 is a conserved genomic region transcribed into a cis -antisense pair of structured lincRNAs, HAR1F and HAR1R , which are specifically expressed in developing cortical neurons [ 68 ]. Global ChIP-seq analysis identified HAR1 as a REST target and, consistent with this finding, showed that both HAR1F and HAR1R are significantly downregulated in the striatum of HD patients [ 69 ].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-coding RNAs have been found to affect the pathobiology of HD or mediate the effects of trinucleotide expansion in its pathophysiology ( Dubois et al, 2021 ; Tan et al, 2021 ). Particularly, two classes of non-coding RNAs, namely microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) have been verified to be abnormally expressed in HD ( Johnson, 2012 ; Dong and Cong, 2021b ; Tan et al, 2021 ). These two classes of non-coding RNAs have been classified based on their size using the cutoff value of 200 nt.…”
Section: Introductionmentioning
confidence: 99%